The Relationship of Learning Interest and Ready to Learn with Learning Outcomes of Midwife Students in Online Learning Methods - Irwanti Gustina; Legina Anggraeni (Universitas Muhammadiyah Enrekang, 2022)
The learning process accompanied by students' interest and readiness to learn determines the achievement of learning outcomes. The learning process consists of theory and practice. Since the enactment of PPKM during the Covid-19 pandemic, the learning process has mostly used online methods. The purpose of this study is to determine the relationship between the interest and readiness to learn from midwifery students in the online method with learning outcomes in the teaching of neonatal midwifery care. The method used is analytics with a cross sectional design. Based on the results of the research, it was found that there was a relationship between interest in learning and readiness to learn with learning outcomes where the p-value was obtained 0.001. To improve learning outcomes requires interest and readiness in learning.